Somatosensory Evoked Potentials and Dopaminergic Responsiveness to Apomorphine and Levodopa in Parkinsonian Patients - M. Miranda; J. L. Castillo; F. Araya (Behavioural Neurology)
Short-latency somatosensory evoked potentials (SSEPs) were recorded from 10 parkinsonian patients in ‘off’ and ‘on’ states induced by apomorphine and levodopa. The effects of apomorphine and long-term levodopa treatment on the frontal N30 component were assessed and compared with healthy controls. Nine of 10 patients tested with apomorphine showed a significant improvement (p